Comparison of dry and cryogenic machining on chip formation and coefficient of friction in turning AISI 4340 alloy steel - A. Raof, Natasha; A. Ghani, Jaharah; Syarif, Junaidi; Che Haron, Che Hassan; Abdul Hadi, Musfirah (Trans Tech Publications Ltd, 2014)
Application of cutting fluid that provides both coolant and lubrication properties in manufacturing operations such as turning, milling, grinding and other processes has been proven to improve the machining output in many aspects. In cryogenic machining, liquid nitrogen (LN2) is used as cutting fluid to reduce the temperature generated at the cutting zone. However, there is still an issue being raised on whether LN2 also functions as a good lubricant as it does as an excellent coolant. Therefore, an intensive study on the chip formation during dry and cryogenic turning of AISI 4340 alloy steel has been conducted to examine the effect of LN2 cutting fluid on the reduction of friction between the chip and the tool. Results from calculation of coefficient of friction indicate that application of LN2 during turning is able to help the friction reduction up to 73%. Smaller value of coefficient of friction indicates that the shear angle is larger which results in smaller shear plane area that provides benefits of lower cutting force needed to shear off the chips and lower cutting temperature being generated during the machining process.